PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP KEMANDIRIAN BELAJAR IPAS PADA SISWA KELAS V SD INPRES TETEBATU KABUPATEN GOWA - Nahda Dzakiyah Nuradillah; Salwa Rufaida; Muhammad Amin Said (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of the Flipped Classroom learning model on the learning independence of IPAS among fifth-grade students at SD Inpres Tetebatu, Gowa Regency. This study employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest design. The research sample consisted of 27 students selected through purposive sampling. The research instruments included a learning independence questionnaire (15 items) and an observation sheet. The data were analyzed using descriptive and inferential statistics, namely the Shapiro–Wilk normality test and paired sample t-test with the assistance of SPSS 29. The results showed that the implementation of the Flipped Classroom learning model had a significant effect on the learning independence of IPAS among fifth-grade students at SD Inpres Tetebatu, Gowa Regency. This was indicated by the increase in the average score of students’ learning independence from 45.26 in the pretest to 85.78 in the posttest. The frequency distribution results showed that before the treatment all students were in the poor category, whereas after the treatment most students were in the good and very good categories. In addition, the results of the t-test obtained a significance value of 0.000 < 0.05 with a t-count value of 12.438. Therefore, it can be concluded that the Flipped Classroom learning model has a significant effect on the learning independence of IPAS among fifth-grade students at SD Inpres Tetebatu, Gowa Regency